Paediatric surgeons’ current knowledge and practices of obtaining assent from adolescents for elective reconstructive procedures - Lai, Krista (Journal of medical ethics, 2023)
Purpose Adolescents develop their decision-making ability as they transition from childhood to adulthood. Participation in their medical care should be encouraged through obtaining assent, as recommended by the American Academy of Pediatrics (AAP). In this research, we aim to define the current knowledge of AAP recommendations and surgeon practices regarding assent for elective reconstructive procedures. Methods An anonymous electronic survey was distributed to North American paediatric surgeons and fellows through the American Pediatric Surgical Association (n=1353). Results In total, 220 surgeons and trainees responded (16.3%). Fifty per cent of the surgeons who are familiar with the concept of assent had received formal training; 12% of the respondents had not heard of assent before the survey. Forty-seven per cent were aware of the 2016 AAP policy statement regarding assent in paediatric patients. Eighty-nine per cent always include adolescents as part of the consent discussion. Seventy-seven per cent solicit an expression of willingness to accept the proposed care from the patient. The majority (74%) of the surgeons perceived patient cooperation/understanding as the biggest barrier to obtaining assent. Over half of the respondents would consider proceeding with elective surgery despite the adolescent patient’s refusal. Reasons cited for proceeding with elective surgery include surgeons’ perception of medical necessity, perceptions of disease urgency, and lack of patient maturity. Conclusion Paediatric surgeons largely acknowledge the importance of assent, but variably practice the principles of obtaining assent from adolescent patients undergoing elective reconstructive procedures. Fewer surgeons are explicitly aware of formal policy statements or received formal training. Additional surgeon education and institutional policies are warranted to maximise inclusion of adolescents in their medical care.